The Relationship of Accuracy of Food Presentation, Atmosphere, Appearance of Food, Outer Food, Taste, and Attitude of The Server with The Leftovers of Staple Foods in Regular and Soft Diet - Putricia, Dita; Yuliantini, Emy; Wahyudi, Anang (jitek, 2023)
The effectiveness of food delivery and service programs can be seen in the patient's leftover food. If excess food is not taken into account and left continuously for a long time, it can impact the patient's nutritional status, which decreases. Malnutrition in patients is closely related to the incidence of food waste in hospitals. This research aims to determine the relationship between the timeliness of serving food, the perception of the atmosphere of the treatment environment, the appearance of food, food from the outside, the taste of food and the attitude of the serving staff with leftover staple foods of ordinary and soft diets. This research used a cross-sectional design carried out in several treatment rooms, namely the Mina room (Class I), Marwah (Class II), and Safa (Class III). The sample in this study was 34 samples. The study's results found a relationship between the appearance of food and food consumption from outside with the remaining staple foods. At the same time, there was no relationship between the timeliness of serving food, the atmosphere of the caring environment, the taste of the food and the attitude of the serving staff with the remaining staple foods. Two variables are related to the six variables studied.